Planning consultant led organisational change - Dohmen, Tammy (My University, 2011)
The contracting of consultancies to lead the implementation of many organisational change projects in the South African public sector has not always led to the successful implementation of these projects. Seeing as the planning process plays a critical role in determining project success, the research was aimed at establishing ways of improving the planning of consultant led organisational change projects in the South African public sector. From a public sector client perspective the key research findings amount to the need for the pro-active management of the consulting relationship and deliverables by the client. From a consultant’s perspective the key research findings amount to the development of a project solution and implementation plan that meets the client’s requirements and can deliver on what it promises. In terms of overall project planning approaches and methodologies, it was found that improvement opportunities do not lie in the implementation of radical new approaches in project management, but rather the disciplined implementation of basic project management principles, processes and methodologies, particularly focusing on the following six main areas; a) obtaining an understanding of the client’s unique environment; b) clarifying and agreeing relevant and realistic project outcomes; c) the formulation of relevant and realistic project plans; d) the establishment of an optimal project team and support structures for the team; e) planning for sustainability; and f) the establishment of project governance frameworks
MBA - WBS
Keywords: Consultants; Organisational change; Public sector